Clinical Significance of Serum Oxidative Stress Markers to Assess Disease Activity and Severity in Patients With Non-Segmental Vitiligo - Li, Shuli; Dai, Wei; Wang, Sijia; Kang, Pan; Ye, Zhubiao; Han, Peng; Zeng, Kang; Li, Chunying (Frontiers in Cell and Developmental Biology, 2021)
Non‐segmental vitiligo (NSV) is a chronic autoimmune disease characterized by progressive depigmentation of the skin. Oxidative Stress (OS) has been proposed as one among the main principal causes in the development and establishment of a sustained autoimmune state in patients with NSV. However, the disease-associated OS biomarkers in clinical practice are not well studied. In this study, we found significantly reduced antioxidant enzymes (catalase, CAT; superoxide dismutase, SOD), total antioxidant capacity (TAC), and increased levels of oxidative DNA damage byproduct (8-hydroxy-2-deoxyguanosine, 8-OHdG) as well as lipid oxidation product malondialdehyde (MDA) in serum of NSV patients compared with healthy controls (HC). Serum TAC, MDA and 8-OHdG levels were correlated with disease activity in all patients with NSV, and much lower in patients receiving conventional treatment in the past 1 year compared to that without treatment. And both serum MDA and 8-OHdG levels were significantly correlated with CXCL10 expression in patients with NSV. In addition, the serum TAC, MDA and 8-OHdG levels were also correlated with affected body surface area (BSA) and Vitiligo Area Scoring Index (VASI) score in patients with NSV. This study demonstrates dysregulated OS status in patients with NSV and provides the evidence that the serum TAC, MDA and 8-OHdG have a capacity to indicate the activity and severity in patients with NSV.